The The effect of a countercyclical Covid 19 policy on the main financial ratios in Islamic rural banks - Maulana, Rizki; Sriyana, Jaka (Jurnal Ekonomi & Keuangan Islam, 2023)
Purpose – This study aims to evaluate the impact of financial services authority’s regulation (POJK) regarding the implementation of Covid-19 Countercyclical in Islamic rural banks. Methodology – This study uses time-series data taken from Financial Services Authority (OJK)’s database covering the period from March 2020 - March 2022. Cointegration test show that there is no cointeggration and the variable is not stationary at the same order/degree, therefore the VAR method is used. Findings – This study reveals that POJK have significant impact on CAR, EAQ, and REO ratios and integrated in the long term. Moreover, this study also find that POJK have a causal or reciprocal effect on CAR and REO which occur in one direction. Futhermore, this study portrays that POJK have a positive impact in returning CAR, EAQ and REO ratios to a positive condition at least 10 months since POJK published, except for CR that before pandemic was in a positive condition. Implications – It is necessary for the BPRS to conduct a stress test on the implementation of the said restructuring and its impact on the finances and ratios of the BPRS as the first step for the BPRS to carry out mitigation if things that are not desired by the BPRS occur. Originality – This paper examines the effect of the implementation of POJK Number 11/POJK.03/2020 which is further amended through POJK Number 48/POJK.03/2020 concerning national economic stimulus as a countercyclical policy impact of the spread of coronavirus disease 2019 on the Islamic rural bank soundness level during Covid 19 pandemic.